Quality in postgraduate medical education: hearing the trainee voice and beyond. (2nd December 2022) - Bogle, Richard; Husselbee, James
Abstract : Most doctors in training will have completed the annual General Medical Council training survey, but what happens to the results and how do they lead to improvement in the quality of training? This article discusses the General Medical Council survey and potential ways in which the assessment of quality in postgraduate medical training could be improved.